Influence of Leadership, Organizational Culture, Work Motivation, and Job Satisfaction of Performance Principles of Senior High School in Medan City - Syamsul Arif; Zainudin Zainudin; Abdul Hamid (Budapest International Research and Critics University, 2019)
This study aims to determine and examine the influence of Leadership (X1), Organizational Culture (X2), Work Motivation (X3), and Job Satisfaction (X4), on the Performance of High School Heads (X5) in Medan. This study also aims to determine the theoretical model of performance (fixed model) that can describe the structure of the causal relationship between the exogonus variable and the endogonus variable. This research was conducted in Medan City High School in 2017, with a total sample of 135 people. The research variable data selection uses a valid and reliable questionnaire based on the results of rational analysis (Expert Judgment) and instrument trials of 32 people from the study population. The data analysis technique used consisted of descriptive analysis, test requirements analysis, and path analysis with a significance level of α of 0.05. The results of the analysis revealed Ho was rejected, Ha was accepted. So, there is a positive and significant direct influence of Leadership, Organizational Culture, Work Motivation, and Job Satisfaction on the Performance of High School Heads in Medan City.